Påtvungen gavmildhed i 2. Korinterbrev - Klostergaard Petersen, Anders (Dansk Teologisk Tidsskrift, 2011)
This brief study on ‘Forced Charity’ discusses aspects of 2 Cor. in lieu of a Durkheimian and Rappaportian theory of culture and religion. I combine these theoretical approaches with a Greimasian semiotic model focused on contractual thinking. It is emphasised that the letter may be conceived of as a rhetorical whole of a symbouleutic nature. Based on its main thesis (1:12-14), the letter aims to move its recipients from a partial to a full understanding. Rather than seeing chapters 8-9 as a haphazard element of the discourse, they constitute the rhetorical turning point of the letter. As indexical token the collection serves rhetorically as proof of the recipients’ willingness to acknowledge Paul’s discursivisation. Although Paul emphasises how God loves a cheerful giver, the collection by virtue of its indexical nature connected to a testing of the recipients’ sincerity is anything but free. It mirrors forced charity.